2020
DOI: 10.1155/2020/8062017
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 Polyunsaturated Fatty Acid Supplementation for Reducing Muscle Soreness after Eccentric Exercise: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Purpose. This systematic review and meta-analysis was performed to determine the effectiveness of Omega-3 polyunsaturated fatty acid (n‐3 PUFA) supplement on muscle soreness after eccentric exercise. Methods. PubMed, EMBASE, CENTRAL, and ISI Web of Science were searched to identify randomized controlled trials (RCTs) that assessed the efficacy of n‐3 PUFA on muscle soreness after eccentric exercise. Mean difference (MD) and the associated 95% confidence interval (95% CI) were calculated by RevMan 5.3 to indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 84 publications
(127 reference statements)
0
7
0
Order By: Relevance
“…Our study demonstrated a significant difference in perceived muscle soreness between groups at 24 h post-EIMD, suggesting N-3 may have experienced less pain compared to PLA group at this point. Previous studies [17,18,47] also found significant differences in DOMS between groups following EIMD, with the fish oil group having reduced muscle soreness. On the contrary, Jakeman et al [17] an acute dose of n-3 PUFA immediately after a muscle-damaging exercise, demonstrated similar muscle soreness between groups.…”
Section: Functional Measurementsmentioning
confidence: 75%
See 1 more Smart Citation
“…Our study demonstrated a significant difference in perceived muscle soreness between groups at 24 h post-EIMD, suggesting N-3 may have experienced less pain compared to PLA group at this point. Previous studies [17,18,47] also found significant differences in DOMS between groups following EIMD, with the fish oil group having reduced muscle soreness. On the contrary, Jakeman et al [17] an acute dose of n-3 PUFA immediately after a muscle-damaging exercise, demonstrated similar muscle soreness between groups.…”
Section: Functional Measurementsmentioning
confidence: 75%
“…Tarbinian et al [ 15 ], Jouris et al [ 16 ] and Jakeman et al [ 17 ] have shown a pain reduction following EIMD with n-3 supplementation. A recent meta-analysis [ 18 ] also concluded that n-3 supplementation could alleviate DOMS after eccentric exercise. Additionally, Atashak et al [ 19 ] reported substantial reduction in CK and in C-reactive protein after lower body resistance exercise following 1 week of 540 mg EPA and 360 mg DHA.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular levels of oleic acid are elevated ( Figure 7(B) ), and its accumulation in the renal cortex has been reported to activate peroxisome proliferator-activated receptors (PPARs) leading to lipid stress and induction of renal injury [ 24 , 25 ]. Polyunsaturated fatty acids (PUFA) undergo auto-oxidation to form oxidized lipids, which a part of them have anti-inflammatory properties [ 26 , 27 ], such as alpha-linolenic acid and docosahexaenoic acid (DHA) derivative ( Figure 7(C,D) ), were shown to have reduced levels. It has been shown that exogenous DHA supplementation significantly altered the oxylipin levels and improved tubular function after ischemia-induced acute kidney injury [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, omega-3 polyunsaturated fatty acids (omega-3 PUFA) supplementation has been suggested for preventing or treating statin myopathy [47] and for inflammation-mediated pain in sarcopenic elderlies [48]. Although a meta-analysis found that supplementation with omega-3 PUFA did not result in a clinically relevant reduction of muscle soreness after eccentric exercise [49], omega-3 PUFA are among the antinociceptive and analgesic natural compounds [50]. The analgesic effect can mask the reported pain due to the statin-induced myopathy.…”
Section: Discussionmentioning
confidence: 99%